CHANGES IN INTRACELLULAR POTENTIALS AND ION FLUXES OF NEURONS OF MOLLUSKS BY EXTRACELLULAR AND INTRACELLULAR ACTION OF SEVOFLURANE AND DESFLURANE - A. I. Vislobokov; E. E. Zvartau; Yu. S. Polushin; V. V. Alferova; I. G. Bukhankov (Вестник анестезиологии и реаниматологии)
Intercellular potentials changes of identifiable intact neurons ini solated CNS of great ramshorn (Planorbarius corneus) have been investigated with the help of intercellular microelectrodes and ion currents of isolated neurons of great ramshorns and pond snails (Lymnaea stagnalis) with the fixation of potential influenced by desflurane in concentrations of 1 and 10 mM (1.2 и 12 MAC) and sevoflurane in concentrations of 1 and 5 mM (2.27 and 11.36 MAC). In 3-5 minutes after the start of anesthetics' action some neurons developed insignificant hyperpolarization (for 2-5 mV), and some other developed depolarization (up to 10 mV). When anesthetics were being washed out for 5-10 minutes the reversible depolarization appeared. Changes in ion currents under the influence of anesthetics were more homogeneous compared to changes in biopotentials. Desflurane and sevoflurane in 1 mM concentrations suppressed amplitudes of sodium, calcium and potassium currents by 40%, and inactivation of potassium low currents was speed up. Anesthetics in the concentration of 5-10 mM suppressed currents by 70-80%. It developed fast (for 20-30 seconds) and after this action the amplitudes restored slowly (for 5-15 minutes) and it failed to reach the initial values in all the times. Intercellular activity of sevoflurane did not suppress ion currents, i.e. it was ineffective.